Ontogenetic and sexual variation of Oecomys bicolor (Rodentia, Cricetidae) from Peru and Ecuador - Menajovsky Bonifaz, Maria Fernanda (2017)
Oecomys is a moderately specious genus of small to medium size. Within the genus, the species O. bicolor is readily recognized; however, it has been reported individual variation in size and color from different populations suggesting that the species could be a species complex. Intraspecific information in O. bicolor is limited despite its wide distribution; but, this information is necessary for delimiting the species as well as explaining variations within populations. Therefore, in the present study 148 specimens of O. bicolor were analyzed, with the objective of evaluating the non-geographic variation of the species related to sex and age. 13 skull-dental variables were analyzed. Univariate and multivariate statistical approximations showed that sexual dimorphism is not significant; on the other hand, the ontogenic variation is considerable among young adults, these results are consistent with previous studies in sigmodontine rodents. It is recommended to continue studies of geographic variation with only ages 3, 4 and 5, and treating males and females collectively.